PENGARUH ELECTRONIC WORD OF MOUTH DAN BRAND IMAGE TERHADAP MINAT BELI MELALUI FITUR TIKTOK SHOP DI PT. XYZ - Defan Cristoper Zebadiah; Erna Mulyati; Agus Purnomo (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
The company PT. XYZ is one of the companies engaged in the TikTok Shop field which provides live streaming agency services to help brands market their products through live streaming platforms, especially TikTok which has been experiencing rapid development in recent times. On the Negative Reviews dashboard there are high reviews, review ratings and cosmetic product reviews are experiencing not good because consumer orders do not match the products received and product ratings at the level of customer satisfaction are quite low for these products and cosmetic product ratings are below 90 % of other competitors. This study uses a quantitative method of multiple linear regression analysis with the aim of testing and analyzing the independent variables on the dependent variable and improving and developing the concepts of independent variables and dependent variables. Besides that, data collection techniques are through observation on social media TikTok Shop, interviews, documentation. Based on results processing data there is influence positive between electronicsword of mouth And brands image to interest buy as big 59.5% temporary there is influenceWhich originate from variable other in outside study This as big 40.5%.